Study of charge density distributions, elastic charge form factors and root-mean square radii for 4He, 12C and 16O nuclei using Woods- Saxon and harmonic-oscillator potentials - Ridha, Arkan R. (Iraqi Journal of Physics, 2019)
The nuclear charge density distributions, form factors and corresponding proton, charge, neutron, and matter root mean square radii for stable 4He, 12C, and 16O nuclei have been calculated using single-particle radial wave functions of Woods-Saxon potential and harmonic-oscillator potential for comparison. The calculations for the ground charge density distributions using the Woods-Saxon potential show good agreement with experimental data for 4He nucleus while the results for 12C and 16O nuclei are better in harmonic-oscillator potential. The calculated elastic charge form factors in Woods-Saxon potential are better than the results of harmonic-oscillator potential. Finally, the calculated root mean square radii usingWoods-Saxon potentials how overestimation in comparison with experimental data on contrary to the results of harmonic-oscillator potential.